Inovasi Layanan Administrasi Keimigrasian untuk Meningkatkan Efisiensi dan Kepastian Hukum - Daffa Raihan Arya Mas’adi (Lembaga Pengembangan Kinerja Dosen, 2025)
Immigration administration services have a strategic role in regulating cross-border mobility while ensuring legal certainty for citizens and foreigners. In the digital era, information technology-based service innovations such as e-visas, biometric systems, and administrative process automation are solutions to improve bureaucratic efficiency. The digital transformation has been proven to be able to reduce waiting times, minimize manual errors, and strengthen the transparency of the service process. However, the acceleration of services does not automatically guarantee legal certainty, because adaptive regulations, good data governance, and clear supervision mechanisms are still needed. This study examines the contribution of immigration service innovations to operational efficiency as well as its implications for legal certainty. Through a qualitative method with a literature review approach, this study identifies international best practices, implementation challenges, and risk mitigation strategies. The findings show that the success of innovation is highly dependent on the integration of technology with regulations, personal data protection, and people's digital literacy. In addition, aspects of cybersecurity and digital inclusion need to be prioritized to avoid access gaps and maintain service fairness. Thus, immigration administrative innovation is not only oriented towards speed and efficiency, but must also ensure the protection of legal rights and administrative accountability.